Effect of Current Density on Properties of Electrodeposited Nickel-Phosphorus Alloy Thin Films - Baskar T; Shaji George; Bashiru Aremu; Digvijay Pandey (AlQalam Journal of Medical and Applied Sciences, 2021)
Electrode position in different current density was used to prepare nanostructure thin films of NiP. Films deposited with NiP have a texture that shows FCC structure. The structural properties of thin films observed experimentally for different current density were compared. The addition of phosphorus (Co) to nickel thin films will improve their structural and mechanical properties. Electrodeposited NiP films were prepared at various current density of 2,3,4 and 5 mA/cm2. Morphological, structural, and mechanical characterization were performed on them. At 5 mA/cm2, the nickel concentration reached its peak of 79.16wt%. As the current density was raised, the nickel content rose. NiP films were bright and evenly coated. NiP film deposits were also nano scale, with an average crystalline size of about 54 nm.